2007
DOI: 10.1083/jcb.200703186
|View full text |Cite
|
Sign up to set email alerts
|

APC mutations lead to cytokinetic failures in vitro and tetraploid genotypes in Min mice

Abstract: Previous research has proposed that genomic instability contributes to cancer progression, with its initiation linked to tetraploid cell formation (Duesberg, P., and R. Li. 2003. Cell Cycle. 2:202–210; Ganem, N.J., Z. Storchova, and D. Pellman. 2007. Curr. Opin. Genet. Dev. 17:157–162). However, there is little direct evidence linking cancer-causing mutations with such events, and it remains controversial whether genomic instability is a cause or an effect of cancer. In this study, we show that adenomatous pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
139
2

Year Published

2008
2008
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(152 citation statements)
references
References 33 publications
11
139
2
Order By: Relevance
“…Recent observations indicate that APC (adenomatous polyposis coli) mutations found in human colorectal cancer may inhibit cytokinesis by preventing mitotic spindle anchoring at the anaphase cortex and thus blocking initiation of cytokinesis. This supports the idea that tetraploidy may represent a first step in genomic instability and eventually cancer [6]. Moreover, it was recently found that abscission mediated via inactivation of the regulatory kinase Aurora B promotes completion of chromosome segregation and thus protects against tetraploidization and cancer [5].…”
Section: Introductionsupporting
confidence: 78%
“…Recent observations indicate that APC (adenomatous polyposis coli) mutations found in human colorectal cancer may inhibit cytokinesis by preventing mitotic spindle anchoring at the anaphase cortex and thus blocking initiation of cytokinesis. This supports the idea that tetraploidy may represent a first step in genomic instability and eventually cancer [6]. Moreover, it was recently found that abscission mediated via inactivation of the regulatory kinase Aurora B promotes completion of chromosome segregation and thus protects against tetraploidization and cancer [5].…”
Section: Introductionsupporting
confidence: 78%
“…Whether the defects we observe in MT dynamics and centrosomes arise from specific loss of p120 or from consequential reduction in other cadherincatenin components in mKers remains unclear. In this regard, it may be relevant that adenomatous polyposis coli is often an associate of AJs because loss of adenomatous polyposis coli function appears to result in genomic instability in colon cancer cells (32,33).…”
Section: Discussionmentioning
confidence: 99%
“…Mitotic dysfunction is often associated with tetraploidization (Caldwell et al, 2007;Ganem et al, 2007). Tetraploid cells are genetically unstable and highly predisposed to the development of aneuploidy during neoplastic progression (Storchova and Kuffer, 2008).…”
Section: Introductionmentioning
confidence: 99%